(3GdGbJUGO GdeYQajs - (3eMeO fGFa(B, (3eMehOs ((3YeGf(B:s (3GdGcGOejhf ddfTQ h GdJhRjY(B,s, 2011)
(3fXQjI GdeYQaI , GdGbJUGO GdeYQaj , GdYhGed GdeDKQI aj eMOOGJ GdGbJUGO GdeYQaj (B: (3GdMhGaR GdGbJUGOjI h GdfXGe GdeDSSj h GdMhceI , GdGHOGY , GdJYdje , JbfjI GdeYdheGJ h GdGJUGdGJs
Keywords: (3GdGbJUGOs; (3GdeYQaIs